(The Ambiguity In Some Jurisprudential Definitions And Its Impact On Not Clarifying Their Meanings) (Journal of the College of Basic Education, 2025)
The research was divided into two sections. In the first section, the researcher dealt with: defining the term (vagueness) and explaining the meaning of the term (jurisprudential definitions). In the second section, he dealt with selected examples of ambiguous jurisprudential definitions, namely: the vagueness in the definition of Salam, usury, the option of condition, and ablution. The aim of the research was to shed light on the vagueness in some jurisprudential definitions and address it by explaining the reason for that vagueness and proposing appropriate alternatives and more correct and clearer definitions for the benefit of students of knowledge and people. The most important results of this research were: 1) One of the most important reasons for the vagueness in jurisprudential definitions is: A) Contemporary authors’ inclusion of definitions in their books prescribed for students of Islamic universities in the manner of definition by logicians by mentioning the genus of the defined, its chapter, its characteristics, and perhaps its general presentation. B) Obtaining ambiguous definitions from the books of ancient and modern jurists in the manner of definition and including them as they are. C) Relying on mentioning words in vague jurisprudential definitions is known to scholars that a single word expresses a lot of jurisprudential information that saves them from citing long phrases in comparison to this word cited by them. This happened from ancient and modern scholars, and contemporary scholars by following them. 2) It became clear from this modest research that the logicians used the method of definition in a deficient manner, which led to not clarifying its meanings and it was very vague and ambiguous for students and people. 3) Scholars cited definitions that are extremely vague and concise in a way that reaches as if the scholar or jurist did not define at all, such that the benefit of the definition is completely negated, such as defining ablution in Islamic law as: (a specific cleanliness). The research recommendations included: 1) Authors and researchers in Islamic jurisprudence should take into account facilitating the jurisprudential definitions in their writings in general and those assigned to university students in particular due to the necessity of that. 2) Authors and researchers in Islamic jurisprudence, in their books prescribed for university students in particular, should not follow in the issue of providing definitions in their books some of the earlier and later jurists who were vague in the definitions. Rather, the correct thing is for them to seek out definitions that are clear and useful to the student of knowledge as much as they are able.